High-Risk Human Papilloma Virus Type 18 Prevalence on Cervical Cancer Patients in Arifin Achmad General Hospital Riau Province (Future Science, 2022)
Cervical cancer is the fourth most common cancer among women globally that is caused by high-risk Human Papillomavirus (hrHPV). One of the most common HPV genotypes causing cervical cancer is HPV 18. However, there is a lack of data regarding hrHPV type 18 prevalence in Indonesia, especially Riau Province. This study aimed to describe the number of high-risk Human Papilloma Virus type 18 cervical cancer patients in Arifin Achmad General Hospital Riau Province. The method used in the study was descriptive with consecutive sampling of HPV 18 of the cervical cancer patients in Arifin Achmad General Hospital from January – July 2022. HPV DNA isolate was identified with a polymerase chain reaction (PCR) test. We recruited 63 women to participate and 32 women (50.79%) were tested for HPV 18. Among the 32 women, the result showed that the most common type of cervical cancer based on the anatomical pathology test was non-keratinizing squamous cell carcinoma (65.625%), keratinizing squamous cell carcinoma (9.375%), and non-keratinizing squamous cell carcinoma invading lymphovascular nodes cervix (6.250%). This study provides descriptive information about the frequency and type of anatomical pathology of cervical cancer caused by HPV 18 among female patients in Riau province. Therefore, it can be used as data in the diagnosis and prevention of HPV in Indonesia.